2013
DOI: 10.2174/1381612811319140007
|View full text |Cite
|
Sign up to set email alerts
|

Targeting UDP-Galactopyranose Mutases from Eukaryotic Human Pathogens

Abstract: UDP-Galactopyranose mutase (UGM) is a unique flavin-dependent enzyme that catalyzes the conversion of UDP-galactopyranose (UDP-Galp) to UDP-galactofuranose (UDP-Galf). The product of this reaction is the precursor to Galf, a major component of the cell wall and of cell surface glycoproteins and glycolipids in many eukaryotic and prokaryotic human pathogens. The function of UGM is important in the virulence of fungi, parasites, and bacteria. Its role in virulence and its absence in humans suggest that UGM is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 98 publications
1
38
0
Order By: Relevance
“…Clearly, substrate affinity is enhanced in the reduced forms of the enzymes. The results are consistent with the previously reported values for other UGMs [10, 16, 37]. In Tc UGM and Af UGM, we have shown that reduction of the enzymes is coupled to conformational changes, mainly in a region known as the histidine loop [18, 22, 38].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Clearly, substrate affinity is enhanced in the reduced forms of the enzymes. The results are consistent with the previously reported values for other UGMs [10, 16, 37]. In Tc UGM and Af UGM, we have shown that reduction of the enzymes is coupled to conformational changes, mainly in a region known as the histidine loop [18, 22, 38].…”
Section: Resultssupporting
confidence: 93%
“…Therefore, enzymes in the Gal f biosynthetic pathway are potential targets for the development of novel anti-parasitic drugs. One important target is the enzyme UDP-galactopyranose mutase (UGM), which catalyzes the conversion of UDP-galactopyranose to form UDP-Gal f (Scheme 1) [9,10]. The importance of this enzyme in kinetoplastids has been validated by demonstration that deletion of the UGM gene leads to greatly reduced virulence in L. major [11].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, eukaryotic UGMs have emerged recently as targets for the design of antifungal, antitrypanosomal, and antileishmanial agents. 24 For example, gene deletion studies have shown that UGM is essential for the virulence of the pathogenic fungus Aspergillus fumigatus and the protozoan parasite Leishmania major . 5,6 Thus, there is interest in characterizing the ligand binding sites of UGMs to facilitate drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…These findings have highlighted the critical role of UGMs in Galf biosynthesis, especially as relates to virulence, cellular adhesion, parasite viability, and proper developmental processes (8)(9)(10)(11). It has been proposed that during the formation of UDP-Galf, a flavin adenine dinucleotide (FAD)-iminium ion intermediate is formed through nucleophilic addition that facilitates galactose ring opening and contraction (5,(12)(13)(14)(15)(16). Three dimensional structures for members of the UGM family have been determined by X-ray crystallography in free form and in complex with various substrates, as well as in association with both oxidized and reduced forms of FAD (12,13,(17)(18)(19).…”
mentioning
confidence: 99%
“…Notably, a covalent FAD-Galp intermediate involved in the UGM reaction has recently yielded to elucidation by X-ray crystallography shedding significant insight into UGM catalysis (20). Consequently, UGM is a potential antimicrobial drug target (3,16).…”
mentioning
confidence: 99%